University and College Counseling Centers' Commitment to Social Justice - Elizabeth M Vera; Julia C Phillips; Suzette L Speight; Thomas M Brounk; Deidre Weathersby; Rufus R Gonzales; Kathy Kordesh (Journal for Social Action in Counseling and Psychology)
The aim of this study was to examine social justice activities of university and college counseling centers. Seventy center directors provided data on their centers’ commitment to social justice activities, the existence and type of prevention services offered, and other indications of social justice efforts. Findings revealed that a vast majority of centers were committed to and engaged in a variety of social justice-related activities, regardless of their staff composition. Size of university was a significant predictor of only selfrated commitment to social justice.